Validitas Aplikasi Gauss Jordan Dimensi 3X3 Berbasis Android pada Materi Sistem Persamaan Linear - Farida, Anisatul; Rohman, Sofyan Nur (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2023)
This study aims to produce a Gauss Jordan application with 3x3 dimensions based on Android which has been tested for validity on linear equation system material for class TI21A4 students, Faculty of Computer Science, Universitas Duta Bangsa Surakarta. This research is a Research and Development (RnD) research that uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects in this study were one mathematics lecturer and one computer lecturer. Data was collected by means of material validation sheets and application displays and interviews. The data analysis used is descriptive qualitative and quantitative descriptive analysis techniques. Based on the results of the validation of the Gauss Jordan 3x3 application in terms of the accuracy of the workmanship, an average score of 4.31 was obtained in the valid category. Assessment of the application display aspect obtained an average score of 4.33 with a valid category. Overall, based on these two aspects, the Android-based Gauss Jordan 3x3 application is said to be valid. Based on the results of the study, it can be concluded that the Android-based Gauss Jordan 3x3 application on the system of linear equations is said to be feasible to use in the learning process in Linear Algebra courses.Keywords: applicaton; gauss Jordan; development; valid; SPL